Keefektifan Biblioedukasi untuk Meningkatkan Efikasi Diri Akademik Siswa VII-A SMPN 3 Krian - Denny Amarta; Cindy Asli Pravesti (Universitas Kanjuruhan Malang, 2021)
The purpose of this study was to determine the differences in students' academic self-efficacy before and after being given Blibioeducation. The research method used was pre-experimental one group pre-test and post-test. The research subjects were 6 students who had academic self-efficacy problems. The data collection instrument used an academic self-efficacy questionnaire. Data analysis in this study used hypothesis testing, namely the Wilcoxon signed rank test. The results of the research conducted by researchers showed that there was a significant difference between the Pre-Test and Post-Test where the Post-Test Academic Self-efficacy was higher than the Pre-Test, which meant that the use of educational bibliography had an effect on increasing academic self-efficacy (sig 0.028 < 0.05). Based on the results of the study, the use of bibliographies has an effect on increasing the academic self-efficacy of seventh grade students of SMP Negeri 3 Krian..